The Significance of Tabayyun Practice as Conflict Resolution in Indonesian Society - David Eko Setiawan (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This article seeks to explain the significance of Tabayyun's practice as conflict resolution in Indonesian society. Indonesia is a multicultural country with considerable potential for conflict. To prevent that, it is necessary to be aware in the community to be open to each other and try to find clarity on a problem/information so as not to cause prolonged conflict. In Islamic Theology, the practice is called Tabbayun. The research problem in this study is the extent to which the significance of Tabayyun's practice can be a conflict resolution in Indonesian society? This research uses a qualitative approach using library methods and is also supported by data from interviews with Muslim figures who have practiced tabayyun in resolving conflicts in society. The results of this study show that tabayyun practice has a very big meaning in solving social conflicts in Indonesian society because it can improve the quality of information conveyed and received, clarify the root causes in a conflict, prevent disasters due to unclear root problems in conflict, and foster social ethics based on religious values in Islamic theology.Artikel ini berupaya menjelaskan pentingnya praktik Tabayyun sebagai penyelesaian konflik di masyarakat Indonesia. Masalah penelitian dalam penelitian ini adalah sejauh mana signifikansi praktik Tabayyun dapat menjadi penyelesaian konflik di masyarakat Indonesia?. Indonesia adalah negara multikultural dengan potensi konflik yang cukup besar. Untuk mencegah hal itu, perlu diwaspadai di masyarakat untuk saling terbuka dan berusaha mencari kejelasan sebuah permasalahan/informasi agar tidak menimbulkan konflik yang berkepanjangan. Dalam Teologi Islam, praktik ini disebut Tabbayun. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode kepustakaan dan juga didukung dengan data hasil wawancara dengan tokoh-tokoh muslim yang telah mengamalkan tabayyun dalam menyelesaikan konflik di masyarakat. Hasil penelitian ini menunjukkan bahwa praktik Tabayyun memiliki arti yang sangat besar dalam penyelesaian konflik sosial di masyarakat Indonesia karena dapat meningkatkan kualitas informasi yang disampaikan dan diterima, memperjelas akar permasalahan dalam sebuah konflik, mencegah bencana karena ketidakjelasan akar permasalahan dalam konflik, dan menumbuhkan etika sosial berdasarkan nilai-nilai agama dalam teologi Islam.